Learning Strategies for SD Muhammadiyah 1 Sidoarjo in the Midst of the Covid-19 Pandemic - Winaldha Maulina; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study is to find out how the strategies used in SD Muhammadiyah 1 Sidoarjo in the covid 19 pandemic. This scientific work examines various aspects, including: history, learning strategies in SD Muhammadiyah 1 Sidoarjo. This research is a descriptive qualitative research. The technique of collecting data and research is through interviews, and observations. Based on the results of research from SD Muhammadiyah 1 Sidoarjo, online learning only lasted for a short time, then the school held face-to-face learning but it was not as effective as before. The impact that has arisen due to COVID-19 on education has changed the education system and curriculum. The curriculum is made in such a way as not to burden students. Apart from the negative impacts, there are also positive impacts, including 1) Teachers become more familiar with technology 2) The emergence of unlimited creativity 3) Trigger the acceleration of educational transformation.